ANALISIS PENGARUH BRAND IMAGE, PRICE DISCOUNT, PACKAGE BONUSES DAN KUALITAS PRODUK TERHADAP IMPULSE BUYING PADA PRODUK ORIFLAME - Afifah Yuliarahma; Andri Nurtantiono (Juremi: Jurnal Riset Ekonomi, 2022)
This study aims to determine the effect of Brand Image, Price Discount, Package Bonuses and Product Quality on Impulse Buying on Oriflame Products. The type of method used in this study is a quantitative method with a non-probability sampling technique. This study used a sample of 97 respondents through the distribution of questionnaires. Data analysis used multiple linear regression analysis using SPSS version 23. The results of this study simultaneously showed that the variable brand image, price discount, package bonuses, and product quality had a positive and significant effect on impulse buying. However, partially the brand image and price discount variables have no positive effect on impulse buying. While the variable package bonuses and product quality have a positive effect on impulse buying.